Reposicionamento de medicamentos em oncologia e doenças infecciosas: avaliação da atividade biológica de dissulfiram e ebselen - Serafin, Marissa Bolson (2022)
Efforts are currently being invested in discovering more effective, selective and innovative antineoplastic and antimicrobial therapies. An alternative, faster process may arise through repositioning, also called drug redirection. Defined as the process of investigating new uses for drugs that have already been clinically approved, it has shown advantages over the traditional search for active substances, such as cost reduction and time to market. Additionally, there is a possibility of the occurrence of synergism of action between combined drugs, which may improve the drug's efficacy, reduces toxicity and provide a broader spectrum of activity compared to monotherapeutic regimens. Thus, this study presents candidate drugs for redirection in oncology, invasive fungal infections and when faced with a pandemic caused by the new coronavirus (SARS-CoV-2). We report the in vitro biological activity of disulfiram and ebselen. The antibacterial activity was determined by evaluating the minimal inhibitory concentration (MIC), minimal bactericidal concentration (CBM) and interaction with standard antibacterials from the checkerboard assay and determination of the Fractional Inhibition Index (FIC). Strains from the American Type Culture Collection and multi-drug resistant clinical isolates (MDR) were used. Cytotoxicity was investigated using cell lines (tumor: murine melanoma - B16F10, human hepatocarcinoma - HepG2, and non-cancer -RAW 264.7) through the assay with 3-(4,5-dimethylthiazol-2-yl)-bromide 2,5-diphenyltetrazolium (MTT). The concentration of dsDNA and production of reactive oxygen species (ROS) in tumor lines after exposure to treatments were evaluated. In the repositioning of drugs in oncology, pharmacological classes such as antibiotics, psychotropic drugs, and antidepressants were indicated for repositioning, mainly for treating glioblastoma, leukemia, breast cancer and multiple myeloma. In terms of repositioning for fungal diseases, among the pharmacological classes, antidepressants, proton pump inhibitors and antivirals stood out, showing activity mainly against Candida, Cryptococcus and Aspergillus genera. In SARS-CoV, SARS-CoV-2 and HCoV-OC43, 22 drugs from different classes showed potential antiviral activity, where repositioning proved to be a promising alternative for treating COVID-19. Disulfiram showed potential antibacterial activity against standard strains and clinical isolates of Enterococcus spp. resistant to vancomycin, showing synergy with the standard antibacterial vancomycin against all strains tested (FICI<0.5). The combination was not cytotoxic against the RAW 264.7 strain. Disulfiram was more cytotoxic against hepatocellular carcinoma (IC50= 9.14) than against melanoma (IC50= 29.36), and its use in conjunction with copper (II) was synergistic against the two tumor cell lines tested. The treatments did not change the presence of dsDNA, and in melanoma ROS production was observed after exposure to disulfiram and this one associated with copper. Ebselen also showed potent antibacterial activity, mainly against Gram-positive positive strains. When associated with ciprofloxacin, there was synergism against all strains tested, especially in Gram negative, where ciprofloxacin started to present active concentrations within the applicable clinical range. Ebselen showed high IC50 values against both tumor cell lines, with ROS production being observed against melanoma. We conclude that drug redirection is a promising approach to cancer, fungal and bacterial infections and to fight COVID-19 and that disulfiram and ebselen are also alternatives for designing new drugs with significant antitumor and antibacterial properties.